Implementasi Pembelajaran Diferensiasi pada Mata Pelajaran Sejarah di SMA N 1 Tomohon - Defano Lumantouw; Meike Imbar; Aksilas Dasfordate (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
At SMA Negeri 1 Tomohon, students are studying history through the lens of differentiated learning, which is the purpose of this study. Students' needs, interests, and learning profiles are taken into account in differentiated learning, which involves adapting the method, content, and learning products. A qualitative technique is used in the study's descriptive methodology. Students are mostly surveyed through the distribution of questionnaires in order to gather data. The study's findings demonstrate that educators are making use of differentiated learning tactics by adapting their pedagogical approaches, modifying student assignments, and incorporating student-specific media into the classroom. Most students respond positively to this approach because they feel more involved and motivated in the learning process. With this study, it is hoped that the differentiated learning process can run well.